Strength and conditioning for cricket fielding: A narrative review - Lim, J.; Wong, S.; McErlain-Naylor, S. A.; Scanlan, A.; Goggins, L.; Ahmun, R.; Comfort, P.; Weldon, A. (Strength and Conditioning Journal, 2023)
The main aim of cricket fielding is to minimize runs scored by the opposing batting team. This is achieved through (a) collecting a batted ball and returning it to the wicket-keeper to prevent runs from being scored, (b) dismissing a batter by catching a batted ball, (c) running a batter out by throwing the ball to strike the stumps, or 4) preventing a batted ball from hitting the boundary. These tasks require various physical fitness attributes, which can be developed through progressive strength and conditioning programming. To support strength and conditioning coaches in developing tailored programs for fielding, this narrative review provides comprehensive information, including a needs analysis, match demands, and injury epidemiology. Furthermore, programming considerations are given for physical testing, program design, and youth fielders. It is recommended to design and implement a well-rounded training program for fielding, focusing on developing a broad range of physical fitness attributes (e.g., aerobic fitness, speed, acceleration, change of direction speed, agility, and upper-body and lower-body strength and power). A combination of traditional weight training exercises and cricket-specific drills can be implemented to achieve this target. This approach allows the training program to meet the specific needs for high- performance fielding.